Statins in pre‐eclampsia or fetal growth restriction: A systematic review and meta‐analysis on maternal blood pressure and fetal growth across species. (20th February 2023) - Meijerink, Lotte; Wever, Kim E.; Terstappen, Fieke; Ganzevoort, Wessel; Lely, A. Titia; Depmann, Martine
Abstract: Background: Several human randomised controlled trials (RCTs) are investigating the effects of statins on pre‐eclampsia (PE) and fetal growth restriction (FGR). This cross‐species meta‐analysis summarises the preclinical evidence of statin use for PE and FGR. Objectives: Evaluate the effects of statins on maternal blood pressure (MBP) and birthweight (BW) in pregnancies complicated by PE or FGR. Search Strategy: PubMed and Embase.com were searched on 10 May 2022 using 'statins' and 'pregnancy'. Selection Criteria: We included RCTs and cohorts with matched control groups as well as animal studies. Data Collection and Analysis: The main outcomes were MBP in mmHg and BW in grams. The standardised mean difference (SMD) with a 95% confidence interval (CI) was calculated. Subgroup analyses on species, statin, dose, timing and route of administration were performed if subgroups included at least three studies. Main Results: Our data included one human and 12 animal studies. Prenatal administration of statins significantly reduced MBP during pregnancy (SMD  −2.49 mmHg [95% CI −4.26 to −0.71], p  = 0.01). There was no significant effect of statins on BW (SMD 0.69 [95% CI −0.65 to 2.03], p  = 0.28). Our subgroup analyses showed no effect on MBP of different doses, species or route of administration. Conclusions: Our cross‐species meta‐analyses demonstrate that statins only reduce maternal blood pressure in rodent pregnancies complicated by pre‐eclampsia or fetal growth restriction and have no effect on birthweight across species. The broad confidence intervals, inconsistent direction of the observed effects across the studies and large risk of bias lead us to conclude that a solid base for further human RCTs is lacking.